(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
The purpose of the study: radiation and hygienic assessment of radon content in the air of residential premises of the Kumkurgan district and substantiation of criteria for ensuring radiation safety of the population. Materials and methods of the study. Radon in the air of public and residential buildings was measured using the Radon FTLAB FRD400 device. The radon meter was installed at 5 points in each measured room. The radon meter for measurements was placed mainly in rooms with the longest stay of residents. Results. The radiation situation in the surveyed buildings of the Kumkurgan district is generally quite acceptable. The situation with population exposure in the Kumkurgan district generally meets the requirements of the Radiation Safety Standards.